The influence of water vapor anomalies on clouds and their radiative effect at Ny-Alesund - Nomokonova, Tatiana; Ebell, Kerstin; Loehnert, Ulrich; Maturilli, Marion; Ritter, Christoph (COPERNICUS GESELLSCHAFT MBH, 2020)
The occurrence of events with increased and decreased integrated water vapor (IWV) at the Arctic site Ny-Alesund, their relation to cloud properties, and the surface cloud radiative effect (CRE) is investigated. For this study, we used almost 2.5 years (from June 2016 to October 2018) of ground-based cloud observations processed with the Cloudnet algorithm, IWV from a microwave radiometer (MWR), long-term radiosonde observations, and backward trajectories FLEXTRA. Moist and dry anomalies were found to be associated with North Atlantic flows and air transport within the Arctic region, respectively. The amount of water vapor is often correlated to cloud occurrence, presence of cloud liquid water, and liquid water path (LWP) and ice water path (IWP). In turn, changes in the cloud properties cause differences in surface CRE. During dry anomalies, in autumn, winter, and spring, the mean net surface CRE was lower by 2-37 W M-2 with respect to normal conditions, while in summer the cloud-related surface cooling was reduced by 49 W m(-2). In contrast, under moist conditions in summer the mean net surface CRE becomes more negative by 25 W m(-2), while in other seasons the mean net surface CRE was increased by 5-37 W m(-2). Trends in the occurrence of dry and moist anomalies were analyzed based on a 25-year radiosonde database. Dry anomalies have become less frequent, with rates for different seasons ranging from -12.8 % per decade to -4 % per decade, while the occurrence of moist events has increased at rates from 2.8 % per decade to 6.4 % per decade.